Distinct Lysosome Phenotypes Influence Inflammatory Function in Peritoneal and Bone Marrow-Derived Macrophages - Kassandra Weber; Joel D. Schilling (International Journal of Inflammation)
Lysosomes play a critical role in the degradation of both extracellular and intracellular material. These dynamic organelles also contribute to nutrient sensing and cell signaling pathways. Macrophages represent a heterogeneous group of phagocytic cells that contribute to tissue homeostasis and inflammation. Recently, there has been a renewed interest in understanding the role of macrophage autophagy and lysosome function in health and disease. Thioglycollate-elicited peritoneal and bone marrow-derived macrophages are commonly used ex vivo systems to study primary macrophage function. In this study, we reveal dramatic baseline differences in the lysosome morphology and function between these macrophage populations and provide evidence that these differences can be functionally relevant. Our results provide important insights into the diversity of lysosomes in primary macrophages and illustrate the importance of accounting for this in data interpretation.